Phytonutrients in the Treatment of Gastrointestinal Cancer. - Khan, Haroon (Sharjah : Bentham Science Publishers, 2023)
Gastrointestinal cancer is one of the most prevalent causes of cancer-related deaths in the world. Recent research demonstrates that phytochemicals are critical in preventing and managing gastrointestinal cancer. The increased intake of phytochemicals could reduce the risk of cancer by inhibiting cancer cell proliferation, inducing apoptosis and autophagy, and suppressing angiogenesis as well as cancer cell metastasis. These mechanisms are also known to counte.
5. NATURAL PHYTOCHEMICALS USED IN CANCER THERAPY -- 5.1. Phytonutrients and Cancer -- 5.2. Mechanism of Anti-Cancer Phytonutrients -- 5.2.1. Anticancer Phytonutrients can be Classified According to their Mechanism of Action -- 5.3. Some Phytoconstituents and their Role in Treating Cancer -- 5.3.1. Indole-3-Carbinol -- 5.3.2. Curcumin -- 5.3.3. Epigallo-Catechin Gallate -- 5.3.4. Crocin -- 5.3.5. Resveratrol -- 5.3.6. Lycopene -- 5.3.7. Sulforaphane -- 5.3.8. Procyanidins -- 5.3.9. Thymoquinone and Dithymoquinone -- CONCLUSION -- CONSENT FOR PUBLICATION -- CONFLICT OF INTEREST -- ACKNOWLEDGEMENTS
Description based upon print version of record.
REFERENCES -- FDA Approval for Phytochemicals in the Treatment of Cancer -- Waseem Raza1,3, Jyoti Singh1,3, Yusuf Hussain1,2, Suaib Luqman1,2 and Abha Meena1,2,* -- 1. INTRODUCTION -- 1.1. What is FDA -- 1.2. FDA Principles and Procedures for New Drug Approval -- 1.3. Clinical Phase Trials -- 1.4. Cancer -- 2. FDA APPROVED PHYTOCHEMICALS -- 3. PHYTOCHEMICALS IN CLINICAL TRIALS -- 3.1. Berberine -- 3.2. Curcumin -- 3.3. Epigallocatechin (EGCG) -- 3.4. Isoflavone -- 3.5. Capsaicin (8-methyl-N-vanillyl-6-nonenamide) -- 3.6. Ginseng -- 3.7. Gossypol -- 3.8. Isoquercetin -- 3.9. Cannabinoids
3.10. Eugenol
eBooks on EBSCOhost
Keywords: Phytonutrients; Gastrointestinal system -- Cancer -- Treatment; Phytonutriments; Tractus gastro-intestinal -- Cancer -- Traitement